2009
DOI: 10.1016/j.bbrc.2009.04.109
|View full text |Cite
|
Sign up to set email alerts
|

The protein content of an adaptor protein, STAP-2 is controlled by E3 ubiquitin ligase Cbl

Abstract: Signal transducing adaptor protein-2 (STAP-2) is a recently identified adaptor protein that contains pleckstrin and Src homology 2 (SH2)-like domains as well as a YXXQ motif in its C-terminal region. Our previous study in T cells demonstrated that STAP-2 influences FAK protein levels through recruitment of E3 ubiquitin ligase, Cbl, to FAK.In the present study, we found that Cbl directly controls the protein levels and activity of STAP-2. STAP-2 physically interacted with Cbl through its PH and SH2-like domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…17) Interestingly, it is also demonstrated that STAP-2 protein expression levels are also regulated by this proteasomal degradation. 18) These lines of evidence indicate that STAP-2 is a potential novel regulator of integrin/FAK-mediated T-cell adhesion (Fig. 5).…”
Section: Stap-2 Modulates T-cell Motilitymentioning
confidence: 89%
See 1 more Smart Citation
“…17) Interestingly, it is also demonstrated that STAP-2 protein expression levels are also regulated by this proteasomal degradation. 18) These lines of evidence indicate that STAP-2 is a potential novel regulator of integrin/FAK-mediated T-cell adhesion (Fig. 5).…”
Section: Stap-2 Modulates T-cell Motilitymentioning
confidence: 89%
“…18) In the case of A431 cells, epidermal growth factor (EGF) induces rapid (5-10 min) translocation of green fluorescent protein (GFP)-fused STAP-2 wild type (WT) protein to the plasma membrane, while mutant STAP-2 that lacks Total RNA samples isolated from these tissues were subjected to quantitative real-time PCR analysis using STAP-1 and STAP-2 primers. Data represent the levels of these mRNA normalized to that of the GAPDH internal control.…”
Section: Reviewmentioning
confidence: 99%
“…STAT5a/b-deficient fetal liver hematopoietic progenitors fail to generate leukemia in recipient mice after retroviral transduction with BCR-ABL (Hoelbl et al, 2006). Among these BCR-ABL-related signaling molecules, we previously found that STAP-2 binds to and regulates c-CBL and STAT5 (Sekine et al, , 2009b. In particular, in a breast cancer model, STAP-2 was found to greatly enhance BRK-mediated STAT5 activation (Sekine et al, 2007b;Ikeda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The SH2-like domain also associates with many signaling molecules, including STAT5, myeloid differentiation factor 88, E3 ubiquitin ligase CBL, focal adhesion kinase and LMP1, as well as Vav1 [16,22,24,27,29,30,31,32]. In the cases of the association of STAP-2 with STAT5 and LMP1, both PH and SH2-like domains are involved.…”
Section: Discussionmentioning
confidence: 99%